Simvastatin ameliorates memory impairment and neurotoxicity in streptozotocin-induced diabetic mice. (4th July 2017) - Fang, Shun-Chang; Xie, Hang; Chen, Fang; Hu, Mei; Long, Yan; Sun, Hong-Bin; Kong, Ling-Yi; Hong, Hao; Tang, Su-Su
Highlights: Simvastatin protects against cognitive dysfunction in streptozotocin-induced diabetic mice. Cognitive dysfunction improvement of simvastatin results from inhibition of neurotoxicity. Inhibition of neurotoxicity of simvastatin is involved in modulation of PPARγ and NF-κB p65. Abstract: Diabetes comes with an additional burden of moderate to severe hyperlipidemia, but little is known about the effects of lipid-lowering therapy on diabetic complications such as diabetes-associated cognitive decline. Herein we investigated the effects of statins on memory impairment and neurotoxicity in streptozotocin-induced diabetic mice. Our data indicated that oral administration of simvastatin at 10 or 20 mg/kg for 4 weeks significantly ameliorated diabetes-associated memory impairment reflected by performance better in the Morris water maze and Y-maze tests. The further study showed that these treatments caused significant increase of peroxisome proliferator-activated receptors gamma and decrease of NF-κB p65 in nucleus of hippocampus and cortex, and ameliorated neuroinflammatory response as evidenced by less Iba-1-positive cells and lower inflammatory mediators including IL-1β, IL-6 and TNF-α as well as suppressed neuronal apoptosis as indicated by decreased TUNEL-positive cells, increased ratio of Bcl-2/Bax and decreased caspase-3 activity in the hippocampus and cortex. Moreover, simvastatin pronouncedly attenuated amyloidogenesis by decreasing amyloid-β, amyloid precursor protein (APP) and beta-site APP cleaving enzyme-1. As expected, treated with simvastatin, the diabetic mice exhibited significant improvement of hyperlipidemia rather than hyperglycemia. Our findings disclosed novel therapeutic potential of simvastatin for the diabetes-associated cognitive impairment.